2009
DOI: 10.1080/09647040802431946
|View full text |Cite
|
Sign up to set email alerts
|

A Colorful Albino: The First Documented Case of Synaesthesia, by Georg Tobias Ludwig Sachs in 1812

Abstract: In 1812, Georg Sachs published a medical dissertation concerning his own albinism and that of his sister. However, he also goes on to describe another phenomenon--namely synaesthesia involving colors for music and simple sequences (including numbers, days, and letters). Most contemporary researchers of synaesthesia fail to cite the case when offering a history of the subject and fewer still will have read it (the original was published in Latin). In this article, we argue that Sachs's case is the first convinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 38 publications
0
33
0
3
Order By: Relevance
“…Comme le relatent Jewanski et collaborateurs, bien qu'ayant déjà été mentionné auparavant, mais sans preuve objective qu'il s'agisse véritablement de cas de synesthésie, cet impressionnant mais mystérieux phénomène attira l'attention de la communauté scientifique dès le XIX e siècle (Jewanski, Day, & Ward, 2009 ;Jewanski, Simner, Day, & Ward, 2011). En particulier, Sachs (1812) décrivit dans sa thèse probablement le premier cas convainquant de synesthésie (il s'agissait vraisemblablement de lui-même) dans la littérature médicale (Jewanski et al, 2009 Jewanski et al, 2009).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Comme le relatent Jewanski et collaborateurs, bien qu'ayant déjà été mentionné auparavant, mais sans preuve objective qu'il s'agisse véritablement de cas de synesthésie, cet impressionnant mais mystérieux phénomène attira l'attention de la communauté scientifique dès le XIX e siècle (Jewanski, Day, & Ward, 2009 ;Jewanski, Simner, Day, & Ward, 2011). En particulier, Sachs (1812) décrivit dans sa thèse probablement le premier cas convainquant de synesthésie (il s'agissait vraisemblablement de lui-même) dans la littérature médicale (Jewanski et al, 2009 Jewanski et al, 2009).…”
Section: Introductionunclassified
“…En particulier, Sachs (1812) décrivit dans sa thèse probablement le premier cas convainquant de synesthésie (il s'agissait vraisemblablement de lui-même) dans la littérature médicale (Jewanski et al, 2009 Jewanski et al, 2009). En 1849, trois nouveaux cas de synesthésie furent rapportés (cités par Jewanski et al, 2011).…”
Section: Introductionunclassified
“…Unlike multiple cases consisting of more than one category of inducers that can be characterised as more or less similar, such as letters and numbers or days of the week and months, poly-aspectual cases are those the triggers of which are functionally more distinct both cognitively and behaviourallye.g., tastes and music, number forms and pain, smell and people's names, etc. In this respect, for instance, Sachs' case in which musical tones had colour and the colours were derived from the names of the notes not from their pitch and timbre per se (Jewanski et al 2009) is a multiple synaesthesia while such drastically different inducers as in a taste-to-colour and a music instruments/ timber-to-colour types can be called poly-aspectual.…”
Section: Domains and Scale Value Identificationmentioning
confidence: 99%
“…In one of the earliest works on synaesthesia, Georg Sachs mentions several categories in one person (himself) (Jewanski et al 2009) without specifically stating the importance of such multiplicity. Later on, Francis Galton reported that, among individual cases, one could find a certain overlapping of different varieties in "the character of the process itself [categories], so that it is by no means uncommon to find two very different forms concurrent [i.e., simultaneously found] in the same person" (Galton 1881: 649).…”
Section: Domains and Scale Value Identificationmentioning
confidence: 99%
“…The first reported case of synesthesia was published in 1812 by Sachs, who documented colored sequences of vowels and music and later Fechner reported colored letter photisms (Jewanski, Day & Ward, 2009;Jewanski et al, 2011). Later research after the Second World War documented growing evidence about synesthetic phenomena and recent findings show that synesthesia is a phenomenon related to various forms of inter-sensory connections from which most frequent form is experience of colored hearing (Martino & Marks, 2001;Nunn et al, 2002;Simner & Hubbard, 2013).…”
Section: Introductionmentioning
confidence: 99%